Perlindungan Hukum Terhadap Anak dalam Proses Peradilan Pidana - Miasiratni, Miasiratni; Bakri, Ilham; Sugara, Randi Kurniawan; Ilham, Muhammad Zikri (Journal of Global Legal Review, 2023)
This study aims to analyze the legal protection provided to children in the criminal justice process in Indonesia. This study uses a normative legal method with a statutory approach and case studies. The main focus of this study is to evaluate the effectiveness of existing laws and regulations and their implementation in protecting the rights of children in conflict with the law, both as perpetrators and victims of criminal acts.  The results of the study indicate that although there have been various regulations designed to protect children in the criminal justice process, their implementation still faces a number of challenges. Some of these include the lack of understanding and training for law enforcement officers, as well as the gap between legal regulations and practices in the field. Therefore, this study recommends increasing the capacity and understanding of law enforcement officers and reviewing existing policies to ensure optimal protection for children in the criminal justice system.